Lire l'Histoire générale des Antilles de J.-B. Du Tertre Exotisme et établissement français aux Îles (1625-1671) - Kullberg, Christina (Francopolyphonies, 2021)
This book examines the historical ramiÿ cations of the concept of exoticism through a literary analysis of Histoire générale des Antilles written by the Dominican missionary Jean-Baptiste Du Tertre. The study gives a thorough account of the early French colonization of the islands and the ways in which this violent process of cultural encounters was represented. It argues for the necessity to reconÿ gure the notion of exoticism, both by revisiting contemporary theorization and by contextualizing it in regard to the history and aesthetics of the times. The study is thus both theoretical, in proceeding by a critical reading of different orientations of exoticism, and historical in offering an in-depth study of an author and a period that have received little attention despite their impact on French Caribbean literature and on the history of anthropology. Readership: The book appeals to researchers and students of French literatures and of travel writing. Anthropologists and historians concerned with the early modern Caribbean will also be interested in this interdisciplinary study.